The Use of Direct Instruction Learning Model Assisted by Phyphox Application Media on Simple Harmonic Vibration Material Experiments - Nurwulan Sari; Tomo Djudin; Ray Cinthya Habellia (Universitas Lambung Mangkurat, 2023)
This study was designed to analyze the effect of using direct instruction model learning with the assistance of the Phyphox application media on simple harmonic vibration material experiments based on students' learning outcomes in terms of factual, conceptual, and procedural knowledge. This research method was a pre-experimental design using the one-group pretest-posttest design type. The samples for this research were the students of class X MIPA Al-Mustaqim who were studying for the 2021–2022 academic year. A saturated sampling technique was used to perform the sampling. The data collection technique for this study was a test consisting of thirteen multiple-choice questions and three essays. The data analysis technique used in this study was the Paired Sample T-Test. The data analysis findings showed that before being given treatment, the average score of factual knowledge was 39.20, conceptual knowledge was 47.60, and procedural knowledge was 44.00. After the treatment, the average score for factual knowledge was 68.80, conceptual knowledge was 67.97, and procedural knowledge was 67.00. The results of hypothesis testing using the paired sample t-test showed differences in the average learning outcomes before and after using the direct instruction learning model assisted by the Phyphox application media in terms of factual, conceptual, and procedural knowledge. Based on these findings, it was determined that the direct instruction learning model with the assistance of the Phyphox application was effective in learning to provide students with opportunities for the successful learning process, with a Cohen's effect size of 1.94 (classified as very high). The direct instruction model of learning with the assistance of the Phyphox application media can be used as input and a reference for teachers who struggle with low student achievement.